STRATEGIC UNCERTAINTY: A NEW WAY OF U.S. DIPLOMACY TOWARDS THE QATAR CRISIS - Andre Wirautomo (Review of International Relations, 2020)
The way of U.S. diplomacy under President Trump administration declared a different approach from the Obama era. As President Trump extols unpredictability as a virtue, where Trump is more active through social media in conveying his views. That behavior considered a boomerang for U.S. diplomacy. Under President Trump’s administration, many of the state statement is contradicted with the White House. The uncertainty of U.S. diplomacy is seen when the United States involved in efforts to resolve the Qatar crisis. Qatar crisis is a diplomatic crisis that occurred between Qatar and the Gulf Arab countries which reached its peak in 2017. The United States has never interfered disputes between Qatar and the Gulf Arab countries that have occurred since 2002. However, the United States increased the tension of the Qatar crisis after several tweets from President Trump criticize Qatar funds terrorism in the Middle East. Simultaneously, Secretary of State Rex Tillerson corrected President Trump's statement by expressing the U.S. is supporting Qatar and trying to help by resolving the conflict as quickly as possible. Qatar is well known as the closest ally of the United States on combating terrorism in the Middle East. The disputes between Qatar and the Gulf Arab countries considered had an impact to be interrupting the movement of the United States on combating terrorism in the Middle East which directly affects several U.S. interests in the region. Differences between President Trump and the State Department do not send a clear nor unified message that is a problem for U.S. strategy towards the Qatar Crisis. It considered as proof of the uncertainty of U.S. diplomacy under President Trump administration. Through this analysis the article seeing the uncertainty of the U.S. diplomacy strategy in resolving the Qatar crisis